Gastric infiltration of hepatic sarcomatoid carcinoma: A case report and literature review - Ma, Shuoshuo; Zhang, Dengyong; Zhao, Guanru; Ding, Sheng; Wu, Qiong; Zhang, Xueli; Lu, Zheng (Frontiers in Surgery, 2023)
Background Hepatic sarcomatoid carcinoma (HSC) is an extremely rare malignant tumor typically observed in clinical settings. HSC occurrence is predominantly noted in the right lobe and rarely in the left lobe of the liver. This report presents a case of sarcomatoid carcinoma that occurred in the left outer lobe of the liver, which was accompanied by gastrointestinal stromal tumors (GSTs) in the greater curvature of the stomach. In addition, the patient showed late-stage recurrence of HSC in gastric tissues. Case presentation A 63-year-old man was concomitantly diagnosed with HSC and GST. The main clinical manifestation was fever. Abdominal computer tomography (CT) and ultrasound-guided percutaneous liver biopsy at the local hospital revealed the presence of malignant hepatic tumors. The patient approached our hospital for further treatment. The subsequent electronic gastroscopy showed multiple submucosal tumors (SMT) in the stomach. Owing to the absence of multiple metastases in other regions of the body, we performed left hepatic lobe resection with gastric partial resection. The postoperative pathological analysis confirmed the presence of HSC and GST. The patient reported feeling well 1 month after the surgery, and no obvious space-occupying lesions in other areas were noted via imaging examinations. However, 3 months later, the patient presented with pain in the upper left abdomen, and examination revealed cancer recurrence in the stomach. The surgery was repeated, and the patient recovered favorably after the procedure. Unfortunately, the patient died owing to multiple metastatic diseases 4 months after the second surgical procedure. Conclusion HSC shows no characteristic clinical manifestations and is highly malignant. Surgical intervention is the first treatment of choice for patients with HSC. In cases of sarcomatoid cancer occurring in the left lobe of the liver, it is imperative to exercise strict vigilance against the tumor's invasion of the stomach tissue. This is particularly important when the tumor breaks through the capsule of the liver.